Mengembangkan Karakter Tanggung Jawab dan Kemampuan Akademik Mahasiswa Melalui Pendekatan Pembelajaran Discovery Learning - Panjaitan, Muktar; Siagian, Asister Fernando; Purba, Yunika Lamtiur (PendIPA Journal of Science Education, 2024)
This research aims to find out how students' character of responsibility and academic abilities develop after implementing the discovery learning learning approach. The subjects of this research were 40 students at HKBP Nommensen Pematangsiantar Elementary School Teacher Education University. This type of research is development research, namely research & development (R & D) based on the procedural model developed by Borg and Gall. Research data was analyzed qualitatively and quantitatively. The data collection techniques are tests and observations. Data were analyzed descriptively and using inferential statistics. The research results show that: (1) The quality of the Learning Event Unit is good; (2) The quality of the Student Activity Sheet is good; (3) The quality of the Learning Results Test is very good; (4) The quality of the Student Responsibility Level Assessment Sheet is good; (5) The quality of the Learning Implementation Observation Sheet is good; (6) The quality of the Activity Observation Sheet is good. It was concluded that students' responsible character and academic abilities improved after using the discovery learning learning approach.